Clarithromycin Solid Lipid Nanoparticles for Topical Ocular Therapy: Optimization, Evaluation and In Vivo Studies - Anroop B. Nair; Jigar Shah; Bandar E. Al-Dhubiab; Shery Jacob; Snehal S. Patel; Katharigatta N. Venugopala; Mohamed A. Morsy; Sumeet Gupta; Mahesh Attimarad; Nagaraja Sreeharsha; Pottathil Shinu (MDPI AG, 2021)
Solid lipid nanoparticles (SLNs) are being extensively exploited as topical ocular carrier systems to enhance the bioavailability of drugs. This study investigated the prospects of drug-loaded SLNs to increase the ocular permeation and improve the therapeutic potential of clarithromycin in topical ocular therapy. SLNs were formulated by high-speed stirring and the ultra-sonication method. Solubility studies were carried out to select stearic acid as lipid former, Tween 80 as surfactant, and Transcutol P as cosurfactant. Clarithromycin-loaded SLN were optimized by fractional factorial screening and 32 full factorial designs. Optimized SLNs (CL10) were evaluated for stability, morphology, permeation, irritation, and ocular pharmacokinetics in rabbits. Fractional factorial screening design signifies that the sonication time and amount of lipid affect the SLN formulation. A 32 full factorial design established that both factors had significant influences on particle size, percent entrapment efficiency, and percent drug loading of SLNs. The release profile of SLNs (CL9) showed ~80% drug release in 8 h and followed Weibull model kinetics. Optimized SLNs (CL10) showed significantly higher permeation (30.45 μg/cm2/h; p < 0.0001) as compared to control (solution). CL10 showed spherical shape and good stability and was found non-irritant for ocular administration. Pharmacokinetics data demonstrated significant improvement of clarithromycin bioavailability (p < 0.0001) from CL10, as evidenced by a 150% increase in Cmax (~1066 ng/mL) and a 2.8-fold improvement in AUC (5736 ng h/mL) (p < 0.0001) as compared to control solution (Cmax; 655 ng/mL and AUC; 2067 ng h/mL). In summary, the data observed here demonstrate the potential of developed SLNs to improve the ocular permeation and enhance the therapeutic potential of clarithromycin, and hence could be a viable drug delivery approach to treat endophthalmitis.